Geo-chemical fractionations of arsenic and lead in the surface sediments of Thuy Trieu lagoon, Khanh Hoa province - Phu, Le Hung; Ha, Dao Viet; Ngoc, Pham Hong; Thu, Nguyen Hong; Dung, Le Trong; Linh, Vo Tran Tuan (Vietnam Journal of Marine Science and Technology, 2019)
The sequential extraction method of Tessier et al. was applied to identify the phase associations of As and Pb in the surface sediment of Thuy Trieu lagoon. The results showed that these two metals were mainly found in the residual fractions. Meanwhile, the carbonate fractions stayed at the lowest portions. Levels of arsenic and lead as Fe-Mn oxide fractions were higher than those as organic fractions and exchangeable fractions. Exchangeable fractions and carbonate fractions of two elements seemed to increase in rainy season. Generally, the mobility of Pb was higher than that of As. In the sediments of Thuy Trieu lagoon, Pb levels cannot currently cause adverse effects on the ecosystems. On the contrary, the risk of As was assessed as moderate level